Impact of grandmultiparity on perinatal outcomes in eastern region of Turkey - Ozkan, Zehra Sema; Atilgan, Remzi; Goktolga, Gulser; Simsek, Mehmet; Sapmaz, Ekrem (Informa Healthcare, 2013)
Objective: It is suggested that grandmultiparity is a troublesome condition in obstetric settings because of increased perinatal complications. Our objective was to compare the incidence of antenatal and intrapartum complications and perinatal outcomes among women who had delivered >= 5 times (grandmultiparous) with those of women who had delivered 1-4 times (parous). Method: A retrospective study was conducted in a university hospital. The study population consisted of age-matched 249 grandmultiparous women and 338 parous women, who had delivered between January 2008 and January 2011. Maternal case records were retrieved and analyzed from the labor ward records. Statistical analysis was done using SPSS version 14.0; chi(2) test was used to analyze categorical variables. Results: The frequencies of hypertensive disorders and gestational diabetes mellitus did not differ between gropus (p>0.05). Obstructed labor, cord prolapse, placenta previa and abruptio placenta were higher in grandmultiparous women. A significantly higher rate of cesarean deliveries was observed in the study population. There was no difference in terms of mode of delivery, prevalence of low and high birthweight (<2.5 and >4 kg) babies, stillbirth, multiple pregnancy and fetal distress. Conclusions: We did not observe an increased incidence of perinatal complications in grandmultiparous women.
Keywords: Complication; grandmultiparity; perinatal outcome